Analisis Kurikulum Merdeka dalam Perspektif Gender : Tinjauan Epistimologi - Siti Nur Maela (Departement of Mathematics Education, 2024)
This research was born from the author's concerns about various cases of sexual violence and bullying in the world of education, for example there were reports of 202 students being victims of sexual violence in the school environment. With the emergence of cases like this, it is necessary to make efforts to disentangle these matters, one of which is through implementing a gender-based curriculum, so that the idea of ​​studying the independence of the curriculum from a gender perspective in epistemological observations emerged. This research aims to 1) analyze how essential it is to implement gender-based values ​​in the independent curriculum in schools, 2) how the epistemological philosophical vision responds to the independent curriculum with a gender perspective. This journal study uses library study by collecting various data sourced from books, journals, articles and certain writings, one of which is data sources related to the curriculum in Indonesia or similar references to obtain valid and actual data. After carrying out the analysis, it was found that the independent curriculum really includes the values ​​of gender equality in it, including: the independent curriculum with a differentiated approach, the P5 Project for Strengthening the Pancasila Student Profile and also in the national assessment of education reports on the Gender Equality Climate assessment. From an epistemological perspective, an independent climate from a gender perspective represents a spirit that is in line with the constructivist learning paradigm. From the results of this research, it is hoped that a curriculum with a gender perspective can be implemented on a massive scale to create a more gender-equitable educational environment.